Dekonstruksi Kewenangan Polisi Kehutanan sebagai Upaya Meminimalisasi Tindak Pidana Pembakaran Hutan Secara Terselubung - Syanindita Nirna Ingtias; Fazal Akmal Musyarri (Jurnal Hukum Lex Generalis, 2021)
Deforestation conditions in Indonesia reached a level of concern. Forests are often burned to open land for the construction of factories or gardens so that there is a transfer of functions that reduce land productivity and reduce the number of forests continuously. These conditions if continuously occur will certainly threaten the sustainability of forests as the heart of nature and cause negative impacts such as floods and landslides. The law prohibits illegal forest burning activities but is ruled out to local communities such as indigenous peoples who burn forests for collective interests rather than profit. The exclusion of vulnerable norms is exploited by irresponsible individuals. Through the provision of the ability to burn forests by local communities, corporations abuse the provision to open land for business activities. On the other hand, the Forestry Police as the institution responsible for forest sustainability does not have the capability to crack down because there is no special authority for the Forestry Police to map and analyze whether a forest fire that occurs is a natural event, done purely by local communities, or is a deliberate burning by corporations by utilizing local communities. Juridical issues in essence become upstream problems related to the criminal act of burning the veiled forest. So in this paper, the author tries to analyze the position and authority of the Forestry Police in cracking down on forest burning criminal acts covertly and recommends the expansion of the main duties and functions of the Forestry Police as a forest rescue strategy for the sustainability of Indonesia's environment for the foreseeable future.